Research in progress—LungSEARCH: a randomised controlled trial of surveillance for the early detection of lung cancer in a high-risk group. Issue 1 (2nd July 2015) - Spiro, Stephen G; Hackshaw, Allan
Abstract : Low-dose CT screening for lung cancer is effective but expensive. Therefore, cheaper or more focused screening strategies may be required. LungSEARCH is a randomised prospective trial of 1568 high-risk individuals (ie, current or former moderate to heavy smokers with mild/moderate COPD) who undergo either annual sputum cytology/cytometry testing or no screening. Those with abnormal sputum then receive annual CT and fluorescent bronchoscopy for the remainder of 5 years, to identify early stage lung cancer. It is hoped that these simple initial tests could identify those requiring expensive CT scans, and the aim is to demonstrate a stage shift towards early stage cancers. Trial registration numbers ISRCTN: ISRCTN80745975, clinicaltrials.gov: NCT00512746 .